Quilombos and Quilombolas in Brazilian psychology: A systematic literature review - Barbosa de Souza , Pedro Henrique; Bonomo, Mariana (Revista de Psicología, 2023)
The present investigation aimed to identify how Quilombos and Quilombolas have constituted themselves as a field of study in Brazilian psychology. Following the guidelines of the PRISMA method for Systematic Literature Review, 38 articles published between 2003 and 2023, available in the LILACS and SciELO databases and in the CAPES Periodicals Portal were selected. The meta-synthesis of the studies was carried out through the categorical-thematic content analysis, with a relative growth in the number of publications from the year 2019 being verified. The results indicated a predominance of themes related to identity processes, in addition to studies focused on the definition of quilombo, reflection on health in communities and the ways in which psychology works in Quilombola territories. Although psychology is not yet constituted as a consolidated field of study on Quilombos and Quilombolas in Brazil, it is evident the need to build theoretical and methodological tools for a psychology “of” quilombo, based on valuing Quilombola knowledge and practices and effective community participation.